How foreign bank entry affect china’s economy? Evidence from banking sector and non-financial firm performance - Yue, Zhang (2020)
This paper is investigating the effects of foreign bank entry into China’s economy through financial and non-financial sectors. The domestic banking industry is selected to represent the financial sector whereas the classification of industrial enterprise from the National Bureau of Statistics of China is chosen as sample of a non-financial industry. The paper also further segregates each respective sector’s data into privately-owned firms and state-owned firms in order to determine the different impacts between them. The panel dataset is used in this paper, the sample duration on the financial sector is from 2007 to 2017, and non-financial sector is from 2009 to 2017. The paper utilizes GRETL techniques to measure the models.